Crystallization and X-ray diffraction data analysis of oxyhemoglobin-I from the catfish Liposarcus anisitsi (pisces) - Smarra, A. L S [UNESP]; Arni, R. K. [UNESP]; De Azevedo, W. F. [UNESP]; Colombo, M. F. [UNESP]; Bonilla-Rodriguez, G. O. [UNESP] (My University, 1997)
Hemoglobin remains, despite the enormous amount of research involving this molecule, as a prototype for allosteric models and new conformations. Functional studies carried out on Hemoglobin-I from the South-American Catfish Liposarcus anisitsi [1] suggest the existence of conformational states beyond those already described for human hemoglobin, which could be confirmed crystallographically. The present work represents the initial steps towards that goal.